Studi Literatur Potensi Pemanfaatan Terak Nikel (Slag Nikel) sebagai Agregat pada Mortar dan Beton - Ratno Wijaya; Sotya Astutiningsih (Universitas Islam 45, 2021)
The increasing of infrastructure development has an impact on increasing demand for construction materials. Generally, construction materials come from nature and still being exploited, which could lead to environmental degradation. Visually, nickel slag resembles gravel and sand which can be used as an alternative material. Therefore, this literature study aims to determine the characteristics and potential utilization of nickel slag gathered from Indonesian lateritic nickel ore and its application as an aggregate in mortar and concrete. The method used in this study is a review of several literatures from a reputable digital publication database with the keywords